Percutaneous metallic stent placement for malignant afferent loop syndrome via the blind end of the jejunal limb after biliary reconstruction - Yozo Sato; Shohei Chatani; Takaaki Hasegawa; Shinichi Murata; Takamichi Kuwahara; Kazuo Hara; Yasuhiro Shimizu; Yoshitaka Inaba (Society of Gastrointestinal Intervention, 2021)
Background : : Malignant afferent loop syndrome occurs after biliary reconstruction and is difficult to treat because of the complicated anatomical changes. The aim of this study was to investigate the safety and efficacy of percutaneous metallic stent placement for malignant afferent loop syndrome via the blind end of the jejunal limb after biliary reconstruction. Methods : : Percutaneous metallic stent placement via the jejunal limb was performed in five male patients (median age, 68 years; range, 51-88 years) with malignant afferent loop syndrome following pancreatoduodenectomy or bile duct resection with reconstruction at our institute from June 2009 to April 2019. Reconstruction was performed using a modified Child's method or the Roux-en-Y method, and blind end of the jejunal limb was surgically fixed to the abdominal wall. Percutaneous drainage of the afferent loop was performed via the blind end of the jejunal limb. Subsequently, percutaneous metallic stent placement was performed via the same route. Technical success, clinical success, and complications were retrospectively evaluated. Results : : Percutaneous metallic stent placement via the blind end of the jejunal limb was successfully achieved in all six procedures. Additional metallic stent placement was performed due to tumor ingrowth in a patient. Drainage catheters were removed from three patients, clamped in one, and could not be removed in one. Clinical success was achieved in four patients (80%) without major complications. Conclusion : : Percutaneous metallic stent placement for malignant afferent loop syndrome via the blind end of the jejunal limb after biliary reconstruction could be a safe and effective procedure.